The impact of leucine-enriched whey protein on skeletal muscle anabolism - Ely, Isabel (2024)
The preservation of skeletal muscle (SKM) throughout the lifespan is vital for maintaining health and well-being. SKM is tightly regulated and maintained by the dynamic relationship between muscle protein synthesis (MPS) and muscle protein breakdown (MPB), with SKM protein turnover occurring at a rate of ~1– 2% per day in healthy younger adults. Protein feeding and exercise are the most potent stimulators of MPS with synergistic action occurring to promote SKM mass through increased MPS and suppressed MPB. However, rates of MPS and MPB are also influenced by physical inactivity and ageing, contributing to SKM atrophy and functional declines.